2019
DOI: 10.1111/mec.15208
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic signatures and co‐occurrence patterns of the ultra‐small Saccharimonadia (phylum CPR/Patescibacteria) suggest a symbiotic lifestyle

Abstract: The size of bacterial genomes is often associated with organismal metabolic capabilities determining ecological breadth and lifestyle. The recently proposed Candidate Phyla Radiation (CPR)/Patescibacteria encompasses mostly unculturable bacterial taxa with relatively small genome sizes with potential for co‐metabolism interdependencies. As yet, little is known about the ecology and evolution of CPR, particularly with respect to how they might interact with other taxa. Here, we reconstructed two novel genomes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 85 publications
(133 reference statements)
6
56
0
Order By: Relevance
“…In addition, some Saccharibacteria were shown to take up oleic acid and to possess lipase and other exoenzymatic activities (Kindaichi et al, 2016). Interestingly, many Saccharibacteria seem to possess a D−lactate dehydrogenase−like protein acting in the conversion of pyruvate into lactate in a fermentation pathway (Lemos et al, 2019). Our data implicate that lactate, the monomer of PLA, might be used as a C source instead of being only a final waste product in the metabolism of some Saccharibacteria.…”
Section: Bacterial Key Taxa Associated With Plasticsmentioning
confidence: 77%
See 2 more Smart Citations
“…In addition, some Saccharibacteria were shown to take up oleic acid and to possess lipase and other exoenzymatic activities (Kindaichi et al, 2016). Interestingly, many Saccharibacteria seem to possess a D−lactate dehydrogenase−like protein acting in the conversion of pyruvate into lactate in a fermentation pathway (Lemos et al, 2019). Our data implicate that lactate, the monomer of PLA, might be used as a C source instead of being only a final waste product in the metabolism of some Saccharibacteria.…”
Section: Bacterial Key Taxa Associated With Plasticsmentioning
confidence: 77%
“…Very little is known about the ecology of Saccharimonadales, which belongs to the candidate phylum Saccharibacteria (formerly TM7), and knowledge almost exclusively stems from genomic data. Saccharibacteria have been shown to possess very small genomes and cell sizes, and they have therefore been proposed to live in symbiosis with other microorganisms depending on co-metabolism (Lemos et al, 2019). Further, Lemos et al (2019) stated that the majority of unique genes found in nearly complete genomes of two Saccharibacteria are of unknown function, underlining the knowledge gaps existing regarding this bacterial order.…”
Section: Bacterial Key Taxa Associated With Plasticsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the NCBI taxonomy database [7], the Microgenomates group at present comprises 16 phylum-level divisions. However, the recently described Genome Taxonomy Database (GTDB) based on genome phylogeny, collapses all CPR lineages into a single candidate phylum, Patescibacteria, comprising the candidate class Microgenomatia [8].Genomics studies of CPR bacteria [4,[9][10][11][12][13][14][15][16] have revealed that they have relatively small genomes (~1 Mbp or less) and limited metabolic capacities, including the common lack of complete pathways for amino acid, nucleotide and lipid biosynthesis, that suggests a partner-dependent symbiotic or parasitic lifestyle [4,17,18]. Physical associations of CPR bacteria with their hosts have been shown for a member of Saccharibacteria (TM7), which attaches to Actinomyces odontolyticus [19].…”
mentioning
confidence: 99%
“…The taxonomy of the contig was predicted to be the Treponema genus, consisting of dozens of species in the human oral microbiota (41). Predicted taxonomy of another contig containing a jumbo prophage was Patescibacteria , the recently proposed Candidate Phyla Radiation (CPR) lineage that encompasses mostly unculturable bacterial taxa with relatively small genome sizes (42), including ubiquitous members of the human oral microbiota (43). Overall, there was no overlap in the predicted taxonomies among the jumbo phages/prophages carrying the phage hallmark genes, suggesting they are not confined to specific phylogenetic groups in the human oral microbiota.…”
Section: Resultsmentioning
confidence: 99%